1990
DOI: 10.1038/ki.1990.175
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular hypertrophy in minimal change disease predicts subsequent progression to focal glomerular sclerosis

Abstract: The study sought a diagnostic clue to identify the group of pediatric patients with apparent minimal change disease who subsequently develop focal glomerular sclerosis (FGS). Review of all renal biopsy material at our institutions identified 42 pediatric patients who met the standard criteria for minimal change disease (MCD) on initial biopsies. Of those, 10 deteriorated clinically and on rebiopsy showed focal glomerular sclerosis (FGS). The initial renal biopsies of these 10 patients were analyzed morphometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
107
0
2

Year Published

1993
1993
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 256 publications
(116 citation statements)
references
References 36 publications
7
107
0
2
Order By: Relevance
“…Although MCD and FSGS can often be differentiated on the basis of clinical course, discrimination of the two entities merely based on clinical symptoms at time of biopsy and histopathology is difficult [94], especially in the case of a small biopsy sample with only non-sclerosed glomeruli. Evidence has been found that glomerular size is relatively high in patients with FSGS [95] and in patients having MCD with an unfavourable prognosis [96]. Molecular research has shown that levels of podocyte-associated components such as dystroglycans [97] and α-actinin 4 532 M Eikmans et al [98] differ between MCD and FSGS in non-hereditary cases.…”
Section: Potential Of Molecular Diagnostics In Nephrological Practicementioning
confidence: 99%
“…Although MCD and FSGS can often be differentiated on the basis of clinical course, discrimination of the two entities merely based on clinical symptoms at time of biopsy and histopathology is difficult [94], especially in the case of a small biopsy sample with only non-sclerosed glomeruli. Evidence has been found that glomerular size is relatively high in patients with FSGS [95] and in patients having MCD with an unfavourable prognosis [96]. Molecular research has shown that levels of podocyte-associated components such as dystroglycans [97] and α-actinin 4 532 M Eikmans et al [98] differ between MCD and FSGS in non-hereditary cases.…”
Section: Potential Of Molecular Diagnostics In Nephrological Practicementioning
confidence: 99%
“…Furthermore, most recurrent cases showed fidelity of histologic phenotype, further supporting inherent pathogenetic mechanisms leading to specific types of FSGS (25). The presence of glomerular hypertrophy in patients with initial diagnosis of apparent MCD predicts an increased risk of subsequently developing overt FSGS (18). More recent molecular studies also support that MCD and FSGS differ from the onset (26).…”
Section: Figure 1 ␤-Dg Expression In Normal Control (A) Fsgs Nos (B)mentioning
confidence: 66%
“…In some patients, large biopsies may show apparent MCD, i.e., lack of segmental sclerosis at first biopsy. However, subsequent course and rebiopsy showed that the ultimate process indeed is FSGS in some of these patients (18). Whether this represents a sclerosing process from the onset or transition from MCD to FSGS is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second phase, the continued glomerular growth was not due to capillary lengthening but, rather, was probably due to an increase in mesangial matrix volume. 28, the kidneys were perfusion-fixed and samples taken for embedding in glycolmethacrylate as described above. Glomerular number and volume were determined using the methods described above.…”
Section: Estimating Capillary Parametersmentioning
confidence: 99%